2006
DOI: 10.2172/881301
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Diffusion Coefficients from ab initio Computations: Hydrogen in Nickel

Abstract: The temperature-dependent mass diffusion coefficient is computed using transition state theory. Ab initio supercell phonon calculations of the entire system provide the attempt frequency, the activation enthalpy, and the activation entropy as a function of temperature. Effects due to thermal lattice expansion are included and found to be significant. Numerical results for the case of hydrogen in nickel demonstrate a strong temperature dependence of the migration enthalpy and entropy. Trapping in local minima a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
3
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 17 publications
5
53
3
1
Order By: Relevance
“…This result closely agrees with results of previous calculations [34,35]. We investigated in detail the influence of quantum corrections [2,32,[34][35][36] using the semi-classically corrected transition state theory [37,38] and found that these corrections are relatively small for Ni and do not affect the results presented here. This investigation will be reported elsewhere [39].…”
Section: H In Bulk Nisupporting
confidence: 91%
“…This result closely agrees with results of previous calculations [34,35]. We investigated in detail the influence of quantum corrections [2,32,[34][35][36] using the semi-classically corrected transition state theory [37,38] and found that these corrections are relatively small for Ni and do not affect the results presented here. This investigation will be reported elsewhere [39].…”
Section: H In Bulk Nisupporting
confidence: 91%
“…For example, they have been used to calculate hydrogen and helium diffusion coefficients in a-Fe [4], nickel [5], a-W [6] and a-Ti [7] at a level of accuracy close to those available from experiments. However, the calculations become tremendously time-consuming when it is applied to helium clusters in metals, during which relatively big supercells are relaxed to equilibrium.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] During diffusion, a migrating atom passes through an energy barrier in moving from a local energy minimum site to another equivalent nearest neighbor site. The energy barrier or migration pathway is commonly thought to follow a bellshaped profile with a "transition state" structure at its peak: this structure possesses a single imaginary frequency in its vibrational spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…The energy barrier or migration pathway is commonly thought to follow a bellshaped profile with a "transition state" structure at its peak: this structure possesses a single imaginary frequency in its vibrational spectrum. Energy profiles that deviate from a bell-shaped profile have been noted commonly for diffusion involving interstitial sites, 7,9,10 and hence the bell-shaped profile is not universal. However, such behavior has not been noted for diffusion in most of the pure elemental solids such as fcc Al, 1 bcc Mo, 4 and hcp Mg. 6 The only observation of the flat shape or even the slightly double-peaked shape profile for vacancy migration was for hcp Zr by Verite et al 11 from first-principles calculations.…”
Section: Introductionmentioning
confidence: 99%